Impact of Stability on Development in Nigeria’s Oil and Gas Sector: Analysing Socio-Economic and Security Implications for Sustainable Growth - Ononokpono, Victor Ononokpono (African Journal of Stability and Development (AJSD), 2025)
This study examined the implications of stability in Nigeria’s oil sector, focusing on its socio-economic and security dimensions. The research explored how a stable oil industry influenced revenue generation, employment, industrial diversification, and security outcomes. The theoretical framework incorporated the resource curse theory and sustainable development theory to contextualise the relationship between oil sector governance, economic sustainability, and security. A qualitative approach was adopted, utilising secondary data from reports, policy documents, and academic publications. Thematic analysis was employed to assess historical patterns and project hypothetical outcomes under stable conditions. Findings revealed that stability in the oil sector significantly enhanced foreign direct investment (FDI), government revenue, and employment opportunities. A well-regulated industry fostered economic diversification by stimulating growth in manufacturing, agriculture, and renewable energy. Additionally, security improved due to a reduction in oil-related conflicts, enhanced government control over illicit trade, and strengthened community-government relations. However, the study identified critical challenges, including governance inconsistencies, environmental degradation, and exposure to global oil market volatility, which hindered long-term stability. To address these challenges, relevant recommendations were made. Strengthening institutional frameworks through policy reforms and independent regulatory oversight is essential to enhancing transparency and investors’ confidence. Enhancing security mechanisms through intelligence-driven strategies and community involvement was necessary to curb vandalism and illicit oil activities. Promoting economic diversification by investing in alternative sectors would reduce dependence on crude oil and build a resilient economy. These measures, if implemented effectively, could foster a stable oil sector that drives Nigeria’s long-term socio-economic and security development.